Development of Interactive Learning Media for Android-Based Correspondence Subjects Using Articulate Storyline 3 - Fitriyah Nur Rohmah; Imam Bukhori (Economics and Education Journal (Ecoducation), 2020)
The pandemic period due to Covid-19 currently demands teachers to be able to use technology as a distance learning medium. But in reality there are still many teachers who have not been able to utilize technology as using learning media. Therefore, the purpose of this research to produce interactive learning media based on Android using articulate storyline 3 on correspondence subjects in SMK Muhammadiyah 5 Kepanjen. This type of research is Research & Development. The data analysis techniques used are qualitative descriptive analytical techniques and quantitative descriptive analyses. The result of this research and development is an Android learning media application that can help facilitate the delivery of materials with additional competency features, quizzes, learning videos, and glossaries that can be accessed offlline as well as the ease of downloading on the web that has been provided equipped with the user manual. This Learning Media has been validated by material experts and media experts whose results are very worthy to use. So that the conclusion of interactive learning media based on Android using articulate storyline 3 on correspondence subjects can be used as learning resources and media support distance learning.